Преобразования Хаара в двоичной системе счисления и на плоскости произвольной размерности - Иванов, В. Г. (НТУ "ХПИ", 2006)
У роботі досліджується можливість розвитку математичних методів швидких перетворень Хаара з метою застосування їх на площині сигналів довільної розмірності і зменшення обсягу обчислень при підсумовуванні рядів Хаара в двоїчній системі числення. У роботі отримані аналітичні вирази для швидких перетворень Хаара в одному і двох вимірах. Отримані вирази дозволяють будувати однорідні обчислювальні середовища перетворень Хаара, структура яких, інваріантна до довжини оброблюваної реалізації.

In work the opportunity of development of mathematical methods of fast transformations of Haar is investigated with the purpose of application them on a plane of signals of any dimension and reduction of volume of calculations at summation of lines of Haar in a binary notation. In work the analytical expressions for fast transformations Хаара in one and two measurements are received. The received expressions allow to build homogeneous computing environments of transformations of Haar , which structure, irrespective to length of processable realization.
Keywords: цифровая обработка сигналов; ортогональные преобразования; матрицы; алгоритмы; вычислительные среды; изображения